2006
DOI: 10.1057/palgrave.jibs.8400203
|View full text |Cite
|
Sign up to set email alerts
|

Does global diversification destroy firm value?

Abstract: Previous empirical studies have found that global diversification results in 18% shareholder loss. In this paper, we examine the sources behind the global diversification shareholder value loss in a contingent claims framework. This postulates that the risk-reduction effects of global diversification should decrease the value of shareholder equity (call option), whereas they should increase bondholder value. Consequently, near-all equity globally diversified firms should not experience a shareholder val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 43 publications
3
60
0
2
Order By: Relevance
“…The arguments for this date back to Cantwell (1999) and the theoretical analysis of Fosfuri and Motta (1999), who show that it can be profitable for technological laggards in a given sector to invest in the home country of more technologically advanced competitors because the potential learning effects are so strong. This also chimes with the more general literature on FDI and performance: for example, Doukas and Kan (2006) relate the sector of the investment in relation to the core technology of the parent, and show that FDI is more successful when firms engage in within-core sectors. There is also evidence that this is linked more generally to the management of technology or knowledge within the firm (Yang et al 2008).…”
Section: Hypothesessupporting
confidence: 71%
“…The arguments for this date back to Cantwell (1999) and the theoretical analysis of Fosfuri and Motta (1999), who show that it can be profitable for technological laggards in a given sector to invest in the home country of more technologically advanced competitors because the potential learning effects are so strong. This also chimes with the more general literature on FDI and performance: for example, Doukas and Kan (2006) relate the sector of the investment in relation to the core technology of the parent, and show that FDI is more successful when firms engage in within-core sectors. There is also evidence that this is linked more generally to the management of technology or knowledge within the firm (Yang et al 2008).…”
Section: Hypothesessupporting
confidence: 71%
“…Villalonga (2004b) estimated the value effect of diversification by matching diversifying and single segment firms on their propensity score and found out that diversification does not destroy shareholder value. In the same direction Doukas and Kan (2006) pointed out that segments acquired by diversifying firms in most cases already traded at a discount before acquisition and hence their acquisition will improve performance, thus refuting the post acquisition negative relationship between diversification and performance in terms of profitability and shareholder value. Others have also shown that high levels of diversification are detrimental to profitability and on average destroy shareholder value for diversifiers pointing to the fact that refocusing generates positive shareholder returns.…”
Section: Diversification and Shareholder Valuementioning
confidence: 98%
“…Academics, consultants, the public and financial community have different views. Some studies such as (Villalonga, 2004a(Villalonga, , 2004bDos Santos, 2008;Doukas & Kan, 2006;Santalo & Becerra, 2008) have been aimed at establishing whether diversification leads to shareholder value destruction or improvement that is, either creating a discount or a premium. Some studies have proved that high levels of diversification increase profitability and shareholder value (Dimitrov & Tice, 2006;Yan et al, 2010;Kuppuswamy & Villalonga, 2010).…”
Section: Diversification and Shareholder Valuementioning
confidence: 99%
See 2 more Smart Citations